Analisis Kejadian Kanker Payudara dan Hambatan dalam Upaya Penanggulangannya - Nilda Elfemi; yullfira Media (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
Solok Regency is one of the districts in West Sumatra Province which has a high number of casesof breast cancer. The aim of the study is to describe the factors which is related to the incidenceof breast cancer and the problems/obstacles in efforts to overcome breast cancer in SolokDistrict, West Sumatra. The research method uses a combination of quantitative and qualitativedescriptive methods. Primary data collection was carried out through direct interviews with breast cancer patients using questionnaires and in-depth interviews with several informants from theHealth Office and Community Health Centers. The results of the study revealed that there werebehavioral factors and patient's habits before the symptoms of cancer diagnosis associated withbreast cancer, including eating patterns and habits. Most of the respondents have a habit ofconsuming foods containing seasonings (95%) and consuming instant noodles/other instant foods(60%). Most of the respondents (60%) had a habit of consuming fatty/cholesterol foods and themajority (90%) rarely consumed fruit/vegetables. Furthermore, most (73%) of breast cancerpatients have a history of using contraception and as many as 30% of patients have a familyhistory of cancer. Problems/obstacles in efforts to overcome breast cancer include the lack ofpublic awareness and knowledge about breast cancer and the existence of behavior, habits andbeliefs of society that do not support a healthy lifestyle and access barriers to health services.The Solok District Health Office must routinely and be integrated to optimize counseling on theprevention and control of breast cancer. There needs to be a policy from the Solok District HealthOffice to fulfill the availability of health workers, the quality of health services, equality andaffordability of health services. It needs improvement of health promotion about breast self-examination more effectively through the use of interesting media. The Community Health Centermust make efforts to regularly increase public awareness and participation in efforts to preventand treatment for breast cancer.Keywords: breast cancer, behavior, obstacle